2017
DOI: 10.3171/2017.7.focus17418
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality associated with hypernatremia in patients with severe traumatic brain injury

Abstract: OBJECTIVEHypernatremia is independently associated with increased mortality in critically ill patients. Few studies have evaluated the impact of hypernatremia on early mortality in patients with severe traumatic brain injury (TBI) treated in a neurocritical care unit.METHODSA retrospective review of patients with severe TBI (admission Glasgow Coma Scale score ≤ 8) treated in a single neurocritical care uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 22 publications
3
59
0
10
Order By: Relevance
“…To date, her group has demonstrated that routinely pushing the cerebral perfusion pressure above 70 mm Hg is inadvisable, and that transfusion of blood to a hemoglobin concentration of 10 g/dl or greater is similarly inadvisable after TBI. This new paper by Vedantam et al 19 promises to do the same for serum sodium values.…”
Section: Editorialmentioning
confidence: 87%
See 1 more Smart Citation
“…To date, her group has demonstrated that routinely pushing the cerebral perfusion pressure above 70 mm Hg is inadvisable, and that transfusion of blood to a hemoglobin concentration of 10 g/dl or greater is similarly inadvisable after TBI. This new paper by Vedantam et al 19 promises to do the same for serum sodium values.…”
Section: Editorialmentioning
confidence: 87%
“…In my opinion, the study by Vedantam et al 19 should particularly cause us to scrutinize the sodium limits associated with hyperosmolar therapies. A serum sodium level of 155 mEq/L (and osmolality of 320 mOsm/L) is generally considered to be the upper limit at which mannitol can be safely administered.…”
Section: Editorialmentioning
confidence: 99%
“…Sodium concentration is the major determinant of the extracellular fluid volume in the body, and it is normally maintained within a narrow physiologic range despite large variations in daily sodium and water intake. Hypernatremiadefined as serum sodium greater than 145mEq/Lis a condition that is commonly observed in patients upon hospital admission, affecting up to 9% of critically ill patients in some hospitals [1][2][3][4][5]. Higher levels of sodium can be associated with a wide range of clinical features which are generally the result of neurological dysfunction due to brain cell shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these major features include confusion or seizures [6]. Moreover, the mortality rate of patients with hypernatremia is significantly higher than that of patients not affected by this condition [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…(139) A ocorrência de DI central, relacionada ou não com morte encefálica, também é frequente e contribui significativamente para a incidência de hipernatremia nestes pacientes. (140) As publicações de estudos sobre a relação entre hipernatremia e TCE são relativamente recentes. Froelich et al (141) publicaram em 2009 um estudo que avaliou prospectivamente 187 pacientes neurocríticos graves (ECG admissão <9), dos quais 30 eram vítimas de TCE, internados em uma UTI neurológica de um hospital terciário de Nova York, com o objetivo de analisar os efeitos do uso de SSH contínua, em comparação ao uso de solução salina a 0,9%.…”
Section: Hipernatremiaunclassified